ANALISIS EFEKTIVITAS PROGRAM INOVASI PEMBERIAN ASI GERSASI DI PUSKESMAS JATI KABUPATEN KUDUS - Salsabilla Rushda Amrina; Septo Pawelas Arso; Nurhasmadiar Nandini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Indonesia has proceeded ASI eksklusif program to create well nutrition generation. The program is held in health services facility. Puskesmas Jati holds the program as GERSASI (Gerakan Ibu Sayang Bayi Wajib ASI). The research objective was to describe and analyze the implementation of the effectiveness of the Exclusive Breastfeeding (ASI) program called GERSASI in Puskemas Jati, Kudus Regency. The objective was to analyze achievement aspect, integration, and adaptation. Research This was descriptive qualitative research, and data collected was done by indepth interview. The research was held on July-August 2020. The informants of the research consist of key informant and triangulation informant. The GERSASI’s Program target were pregnant mothers and breastfeeding mothers in Jati kulon village. GERSASI program performs socialization in Jati Kulon village in March 2017. The consensus was done by Jati Kulon authority to Jati Kulon villagers. The infrastructure of GERSASI Program were monitoring books, stickers, and certificates. Accompaniment was done by health cadres who were breastfeeding motivators. The health cadres were chosen because they were considered to be closed to the community. The effectiveness of the GERSASI Program is still deemed ineffective. There were still several aspects that need to be improved so that the GERSASI Program can achieve its objectives.